INTRACRANIAL ANEURYSMS IN CHILDREN - A NEW PERSPECTIVE - Alexandru Vlad Ciurea; H. Ples; Nicolaie Dobrin; Andrei Adrian Popa; Bogdan-Gabriel Bratu; Antonio-Daniel Corlatescu (Romanian Neurosurgery)
Introduction